Effect of rigor state and curing temperature on the processed yield and physicochemical properties of broiler meat (2016)
A study was conducted using 16 (sixteen) half carcasses of broiler chickens with the aim of improving the yield and quality of meat products. The effects of rigor state and curing temperature on yield and quality of smoked-cooked meat were investigated using a 2 x 2 factorial arrangement. The meat was cured pre-rigor and post-rigor in hot and cold brine solution, after which they were smoked for approximately two hours to an internal temperature of 69±1ºC. The results showed that rigor states significantly (P<0.05) affected dry matter, moisture, lipid and nitrite content. Lower moisture (20.23 %) and lipid content (10.37 %) was observed in the post-rigor meat but with higher nitrite content (131.06 ppm). Curing temperatures significantly (P<0.05) affected the yield, dry matter, moisture, nitrite and salt contents of the product. The yield of meat and moisture content was higher in cold cure (14.60 % and 32.68 % respectively) but with a lower nitrite and salt content. Furthermore, the interaction between curing temperature and rigor state was also significant (P<0.05) with post rigor and cold cure interacting best with a yield of 15.88 % and lipid content of 10.35 %. Lowest moisture content was observed in the post-rigor hot cure treatment (15.49 %). Nitrite and salt contents were lower in the pre-rigor cold cure treatment (108.90 and 1.86 % respectively) with also higher ash content (5.62 %). It is concluded that optimum yield can be achieved through cold curing in post- rigor state.